2010
DOI: 10.1002/lsm.20974
|View full text |Cite
|
Sign up to set email alerts
|

Fractional ablative carbon dioxide laser resurfacing for skin rejuvenation and acne scars in Asians

Abstract: Ablative fractional CO₂ laser resurfacing was overall safe and effective for skin rejuvenation and acne scars in Asians. However, in view of the high post-inflammatory rate and the statistically significant but only mild to moderate improvement after a single treatment as observed in this study, there is a need to review the current role of fractional ablative CO₂ laser treatment as compared to fractional non-ablative for skin rejuvenation and acne scar treatment in Asians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
98
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(107 citation statements)
references
References 36 publications
6
98
1
1
Order By: Relevance
“…In study by Simin et al, 13 85% patient showed 30 -70% reduction in acne scars which is comparable with our study in which 96.7% patients showed 25 -80% reduction in acne scars. In study by Chan et al, 14 86% patient showed good and fair efficacy. In study by Manuskiatti et al, 15 85% patients showed more than 25% reduction in acne scars.…”
Section: 12mentioning
confidence: 91%
“…In study by Simin et al, 13 85% patient showed 30 -70% reduction in acne scars which is comparable with our study in which 96.7% patients showed 25 -80% reduction in acne scars. In study by Chan et al, 14 86% patient showed good and fair efficacy. In study by Manuskiatti et al, 15 85% patients showed more than 25% reduction in acne scars.…”
Section: 12mentioning
confidence: 91%
“…PIH rates in darker skin types III, IV, and V have been as high as 50%, 55.5%, and 92%, respectively, after fractional CO2 treatment. 39,42,43 PIH has been associated with higher-density settings. [44][45][46] Nonablative fractional lasers NAFLs utilize a wavelength of light in the midinfrared spectrum that penetrates into the midreticular dermis, inducing new collagen formation and tissue remodeling.…”
Section: Safety and Adverse Eventsmentioning
confidence: 99%
“…Side effects did not vary depending on underlying condition or skin type, except for PIH, which occurred with an increased frequency in patients with darker skin types. 73 Similar to AFLs, lower densities and fewer treatment passes have been associated with a lower risk for hyperpigmentation at the expense of more treatment sessions, 43 whereas higher densities result in more side effects without improved results. 40 Pre-and posttreatment with hydroquinone 4% may help decrease the incidence of PIH, even in darker patients.…”
Section: Safety and Adverse Eventsmentioning
confidence: 99%
“…Up to 1 mm in depth can be achieved with fractionated CO 2 , thus inducing greater collagen production and dermal remodeling than nonablative fractionated photothermolysis [42]. Persistent collagen remodeling with wound healing response occurs up to 3 months after in vivo fractional CO 2 ablative laser [43].…”
Section: Atrophic Acne Scarsmentioning
confidence: 99%